Um olhar para além da pobreza: fatores de risco e proteção para o desempenho cognitivo de adolescentes em situação de vulnerabilidade social - Silva, Verônica Santos da (2016)
The general purpose of this work is to indicate the need for neuropsychological assessment tools present a regulation that considers the socioeconomic level, in view of the impact that growing up in socially vulnerable situation generates on cognitive performance. Counted with the participation of 96 teenagers, aged between 12 and 14 years (average = 13 and standard deviation = 0.80), regularly enrolled in primary education in public schools and private basic education in the city of Jequié, interior of Bahia, (n = 41, and 11 private schools and 30 public school) and Palmeiras dos Índios, interior of Alagoas (n = 55, and 28 private schools and 27 public school). The participantshave been informed about the anonymity and confidentiality of their answers and was obtained the free consent of all participants. The data were gathered and submitted to statistical analysis using the SPSS software (version 22). The results indicate the effect of income as a protective factor for the performance in the perception of functions, language, executive functions, arithmetic skills and guidance space-time. It was also used the binding criteria in the BolsaFamília Program (PBF) as analysis variable, in which indicated that the BF's presence is associated with an indicative performance profile of important severity of deficits for all functions evaluated in adolescents of Bahia, with exception of executive function, that is justified by the socioeconomic profile of the program linked to the population. The results also show that the functions of memory, attention and Praxis allows to identify that these functions, the presence of deficits in cognitive performance does not present a pattern that can be associated with socioeconomic level. It trusts that the results identifying the impact of social vulnerability condition on cognitive performance, indicating that variable as a risk factor considered in neuropsychological evaluations. It argues that will be possible to identify initial aspects that will benefit for further investigation of the relationship between social vulnerability status and cognitive performance in its various functions. Thus, the relationship between cognitive deficits and social vulnerability exploredpreliminarilyin this research, allowing initial inferences about the contribution of each aspect that makes up the social vulnerability as construct complex on cognitive performance. Itsuggest for future studies, the increased of sample and the inclusion of control mechanisms that allow measure the effect of social vulnerability on each of the displayed performance profiles.